Community Empowerment through Rang Mudo Farmers Group: Efforts to Improve the Economy in Nagari Paninjauan - Mulyani Mulyani; Irwandi Irwandi (Mangabdi: Journal of Community Engagement in Religion, Social, and Humanities, 2024)
The community service program through the Rang Mudo Farmers Group in Nagari Paninjauan aims to improve farmers' economic well-being through community-based empowerment. The method employed is a participatory approach involving the government, private institutions, and the local community in various stages, including needs assessment, training, and program implementation. This service focuses on enhancing farmers' technical capacities, strengthening social networks, and expanding market access. The results indicate that farmers have increased productivity and income through the adoption of modern agricultural technologies, the use of subsidized fertilizers, and marketing collaboration. The program also successfully built solidarity among group members, created new job opportunities, and improved the competitiveness of agricultural products in regional markets. In conclusion, this community service not only boosted farmers' economic well-being but also strengthened social capital that supports the sustainability of farming communities in Nagari Paninjauan.